Corneal dendritic cells and the subbasal nerve plexus following neurotoxic treatment with oxaliplatin or paclitaxel - Jeremy Chung Bo Chiang (Nature Portfolio, 2021)
Abstract Immune cell infiltration has been implicated in neurotoxic chemotherapy for cancer treatment. However, our understanding of immune processes is still incomplete and current methods of observing immune cells are time consuming or invasive. Corneal dendritic cells are potent antigen-presenting cells and can be imaged with in-vivo corneal confocal microscopy. Corneal dendritic cell densities and nerve parameters in patients treated with neurotoxic chemotherapy were investigated. Patients treated for cancer with oxaliplatin (n = 39) or paclitaxel (n = 48), 3 to 24 months prior to assessment were recruited along with 40 healthy controls. Immature (ImDC), mature (MDC) and total dendritic cell densities (TotalDC), and corneal nerve parameters were analyzed from in-vivo corneal confocal microscopy images. ImDC was increased in the oxaliplatin group (Median, Md = 22.7 cells/mm2) compared to healthy controls (Md = 10.1 cells/mm2, p = 0.001), but not in the paclitaxel group (Md = 10.6 cells/mm2). ImDC was also associated with higher oxaliplatin cumulative dose (r = 0.33, p = 0.04) and treatment cycles (r = 0.40, p = 0.01). There was no significant difference in MDC between the three groups (p > 0.05). Corneal nerve parameters were reduced in both oxaliplatin and paclitaxel groups compared to healthy controls (p < 0.05). There is evidence of elevation of corneal ImDC in oxaliplatin-treated patients. Further investigation is required to explore this potential link through longitudinal studies and animal or laboratory-based immunohistochemical research.